2012
DOI: 10.1038/hdy.2012.107
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the chromosomal radiation of Madeiran house mice: a microsatellite analysis of metacentric chromosomes

Abstract: Chromosome races of Mus musculus domesticus are characterised by particular sets of metacentric chromosomes formed by Robertsonian fusions and whole-arm reciprocal translocations. The Atlantic island of Madeira is inhabited by six chromosome races of house mice with 6-9 pairs of metacentric chromosomes. Three of these races are characterised by the metacentric 3.8 also found elsewhere in the distribution of M. m. domesticus, including Denmark and Spain. We investigated the possibility that metacentric 3.8 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
(79 reference statements)
1
20
0
Order By: Relevance
“…However, several studies have addressed this question by measuring the level of divergence of mapped microsatellite markers between chromosomally differentiated house mice. In all cases, centromeric loci exhibited higher differentiation levels than distal ones, regardless of the type of meiotic heterozygosity of the hybrids, that is, complex chains or rings (Panithanarak et al, 2004;Förster et al, 2013;Gimenez et al, 2013 ) or trivalents (Franchini et al, 2010). Previous studies have indicated that recombination suppression extended up to 15-20 cM from the centromere depending on the chromosomes involved in the Rb fusion and the genetic background (Davisson and Akeson, 1993;Gimenez et al, 2013;Capilla et al, 2014).…”
Section: Effect Of Rb Heterozygosity On Gene Flowmentioning
confidence: 99%
“…However, several studies have addressed this question by measuring the level of divergence of mapped microsatellite markers between chromosomally differentiated house mice. In all cases, centromeric loci exhibited higher differentiation levels than distal ones, regardless of the type of meiotic heterozygosity of the hybrids, that is, complex chains or rings (Panithanarak et al, 2004;Förster et al, 2013;Gimenez et al, 2013 ) or trivalents (Franchini et al, 2010). Previous studies have indicated that recombination suppression extended up to 15-20 cM from the centromere depending on the chromosomes involved in the Rb fusion and the genetic background (Davisson and Akeson, 1993;Gimenez et al, 2013;Capilla et al, 2014).…”
Section: Effect Of Rb Heterozygosity On Gene Flowmentioning
confidence: 99%
“…Nuclear sequence data, including from the Y chromosome, have often been used for studies involving multiple subspecies or species (Boissinot & Boursot, ; Geraldes et al ., ) but not generally extended to within‐subspecies phylogeographical history, often as a result of insufficient polymorphism. Where more recent phylogeographical studies have used additional non‐mtDNA markers, these have tended to be autosomal microsatellites that have been useful to examine population‐level genetic parameters of the study populations but, so far, they are of less value for inferring colonization history (Hardouin et al ., ; Jones et al ., , b, ; Förster et al ., ; Gabriel, Mathias & Searle, ). There is further potential for nuclear studies from large‐scale house mouse single nucleotide polymorphism arrays (Yang et al ., ); these could provide a reliable phylogeographical history for the autosomes, although the cost of the chips may be prohibitive for phylogeographical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Boro-din et al [2008] detected a reduction in CO frequency in translocated chromosomes of the common shrew, whereas others reported a reduction in both chiasmata number and COs in house mice due to Robertsonian translocations [Castiglia and Capanna, 2002;Dumas and BrittonDavidian, 2002;Capilla et al, 2014]. On the contrary, indirect evidence for the suppression of recombination has included the analysis of rates of genetic divergence and recombination between rearranged and collinear chromosomes [Navarro and Barton, 2003;Franchini et al, 2010;Farré et al, 2013;Förster et al, 2013;Giménez et al, 2013]. This latter approach has been used in several studies on Drosophila [Kulathinal et al, 2008], Helianthu s sp.…”
Section: Chromosomal Rearrangements As Recombination Modifiersmentioning
confidence: 99%